PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP KINERJA MANAJERIAL SKPD DENGAN DESENTRALISASI DAN GAYA KEPEMIMPINAN SEBAGAI VARIABEL MODERATING (STUDI PADA SATUAN KERJA PERANGKAT DAERAH KOTA DUMAI) - Trino Rizandi; Azwir Nasir; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Managerial Performance local work unit is a picture of the level of achievement of goals or objectives as the elaboration of the vision, mission, and strategy of local government agencies that indicate the success or failure of the implementation of activities in accordance with the duties and functions of the government apparatus. This study aims to look at the effect of budgetary participation and budget goal clarity on the managerial performance of government agencies with decentralized and leadership style as a moderating variable in Dumai. Method of determining the sample using purposive sampling totaling 90 people. The results found that the budgetary participation and budget goal clarity significant and positive impact on Managerial Performance. Interaction with decentralized moderate budgeting participation effect on managerial performance. However, the interaction of budget participation with leadership style and budget goal clarity interaction with decentralization and with leadership style no effect on managerial performance.Keywords: Budgetary Participation, Budget Goal Clarity, Managerial Performance, Decentralization and Leadership Style.